Structures of the fibrous dolomite crystals in methane seep carbonates from Marmorito, northwest Italy - Lu, Yang; Paulmann, Carsten; Mihailova, Boriana; Malcherek, Thomas; Birgel, Daniel; López Correa, Matthias; Lin, Zhiyong; Lu, Liuyi; Milker, Yvonne; Peckmann, Jörn (In: Lu, Y et al. (2023): MgCO₃ contents, structure, and carbon and oxygen isotope compositions of fibrous crystals in a Miocene methane seep carbonate [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963595, 2023)
Samples were made into 100 μm rock slices. Points of interest were aligned to the beam and measured with φ scans +/− 25° at χ = 0°, 30°, 60° and 90°, respectively. Stepsize of φ was 1° and exposure time was 10 seconds. Results were converted to powder diffraction diagrams by the CrysAlisPro software package.
Keywords: carbonate cement; Fibrous dolomite; methane seep; Miocene; SD-AOM